Enfrentamiento del cólico renal en Urgencia - González B. , Ulises; Díaz P., Carla; Martínez O., Matías (Revista Hospital Clínico Universidad de Chile, 2014)
Ureteral colic as a nosologic entity, is part of a select group of pathologies that present themselves in an intense and acute form, in which the patient suffers excruciating pain and demands quick diagnosis and treatment. It’s also a common disease in our emergency service, like in other countries. The aim of the present study is to standardize and deepen the management and treatment of ureteral colic, from the perspective of the emergency medicine.